Longitudinal association between obesity and periodontal diseases among secondary school students in Hong Kong: a prospective cohort study - Ling-Wei Li; Hai Ming Wong; Colman P. McGrath (BMC, 2018)
Abstract Background There is no consensus opinion regarding the association between obesity and periodontal diseases among children and adolescents in the literature. Methods A prospective observational cohort study was conducted in a Hong Kong cohort at age 12, 15 and 18. CPI and various obesity indices including BMI, WC, WHR, WHtR, and TRSKF were recorded during each wave of data collection. Information on socioeconomic status and oral health behaviors were collected through self-completed questionnaires. Results Two hundred and eighty-two (male: 122 and female: 160) participants completed all three rounds of data collection. Prevalence of overweight/obesity was 27.0, 19.1, and 14.2% at 12, 15, and 18 years, respectively. 19.9% participants had healthy periodontal conditions at age 12. While the percentage dropped to 10.3% at 15 years and 5.7% at 18 years. The proportion of 15-year-old adolescents who brushed teeth more than twice a day was significantly higher among participants belonging to the lower BMI, WC, WHR, and WHtR category (P < 0.05). The fully adjusted model revealed that participants with lower BMI at age 15 had higher probability of having more than 50% index teeth free from periodontal diseases at age 18 (OR: 2.78; 95% CI: 1.16, 6.64; P = 0.022). Conclusions Although higher BMI at 15 years was associated with more extensive periodontal inflammation at age 18, this was believed to be an indirect association confounded by the poor oral health care among overweight/obese individuals. Oral health promotions should be directed to improve periodontal conditions of overweight/obese secondary school students.